Makúk: A New History of Aboriginal-White Relations - Lutz, John S. (UBC Press, 2008)
The history of Aboriginal-settler interactions in Canada continues to haunt the national imagination. Despite billions of dollars spent on the "Indian problem," Aboriginal people remain the poorest in the country. Because the stereotype of the "lazy Indian" is never far from the surface, many Canadians wonder if the problem lay with "Indians" themselves. John Lutz traces Aboriginal people's involvement in the new economy, and their displacement from it, from the first arrival of Europeans to the 1970s. Drawing upon oral histories, manuscripts, newspaper accounts, biographies, and statistical analysis, Lutz shows that Aboriginal people flocked to the workforce and prospered in the late 19th century. The roots of today's wide-spread unemployment and "welfare dependency" date only from the 1950s, when deliberate and inadvertent policy choices--what Lutz terms the "white problem"--drove Aboriginal people out of the capitalist, wage, and subsistence economies, offering them welfare as "compensation." -- Publisher's description. Contents: Introduction: Molasses stick legs -- Pomo Wawa: the other jargon -- Making the lazy Indian -- The Lekwungen -- The Tsilhqot'in -- Outside history: labourers of the aboriginal province -- The white problem -- Prestige to welfare: remaking the moditional economy -- Conclusion: the outer edge of probability, 1970-2007 -- Postscript: subordination without subjugation.
Keywords: British Columbia; Commerce; Commerce. Indians of North America; Economic conditions. Indians of North America; Employment; Employment. Indians of North America; Government relations. Indians of North America; Government relations. Whites; History. Indians of North America; Whites